Efektivitas Teknik Restrukturisasi Kognitif dalam Konseling Individual untuk Mereduksi Perilaku Merokok - Yusadri Yusadri; Alfi Rahmi; Intan Sari (Program Studi Bimbingan dan Konseling FKIP UMSU, 2020)
The aim of this research is to find out the effectiveness of cognitive restructuring techniques in individual counseling to reduce the smoking behavior of students in SMA N 1 Batipuh. This research is a Pre Experiment One Group Pretest Posttest Design model. The population is students of class XI IPA and XI IPS as many as 20 people, while the study sample is students of class XI IPA as many as 5 people and are indicated to have smoking behavior based on non rondom sampling techniques and recommendations from BK teachers. Data collection instruments are in this study a Likert scale. Data analysis techniques using non-parametric statistical tests using Wilcoxon rank test, hypothesis testing using Statistical Product and Service Solution (SPSS) version 20. The results of research that have been known from the results of the Z (Wilcoxon) test values show the difference between the pretest and posttest scores. From the Wilcoxon test calculation results obtained a significance value of Sig p-value of-2.032. Based on the applicable provisions, it is known that the Wilcoxon Sig p-value test result is 0.042 <α (α = 0.05) which means that Ha is accepted and Ho is rejected. From the calculation results of the Wilcoxon test it can be concluded that individual counseling using cognitive restructuring techniques can reduce student smoking behavior.